Mechanism of Oncogenic Transformation by Rous Sarcoma Virus III. Role of Proviral DNA in Morphologic Conversion of Chicken Embryo Fibroblasts - Balduzzi, Piero C. (1973)
Multiplication of Rous sarcoma virus and morphological conversion of chicken embryo fibroblasts are mediated by a DNA provirus. The role of the provirus in induction of morphological conversion has been shown by experiments of light inactivation of bromodeoxyuridine (BUdR)-sensitized proviral DNA. In the experiments reported here, inactivation of focus formation by BUdR and light could be obtained in cells in which the ability to produce virus has become resistant to X irradiation. This property is considered here to reflect the integrated state of the provirus. These experiments indicate that the role of proviral DNA extends beyond induction of morphological conversion and that an intact provirus is required for the maintenance of the transformed state. These experiments also indicate that no irreversible process leading to morphological conversion is initiated by a nonintegrated or by an integrated provirus.